2021
DOI: 10.1177/16878140211044929
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-precision grinding of 4H-SiC wafer by PAV/PF composite sol-gel diamond wheel

Abstract: To eliminate the deep scratches on the 4H-SiC wafer surface in the grinding process, a PVA/PF composite sol-gel diamond wheel was proposed. Diamond and fillers are sheared and dispersed in the polyvinyl alcohol-phenolic resin composite sol glue, repeatedly frozen at a low temperature of −20°C to gel, then 180°C sintering to obtain the diamond wheel. Study shows that the molecular chain of polyvinyl alcohol-phenolic resin is physically cross-linked to form gel under low-temperature conditions. Tested by mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The main function of the pyrolytic carbon interface is to protect the carbon fiber from damage during chemical vapor deposition, explaining the removal mechanism of the C f /SiC composite in this experiment does not distinguish it from the SiC matrix. 39 The main mechanical properties 38,39,44 of C f /SiC composite and its main compositions at room temperature are shown in Table 1. It can be found that the axial mechanical strength is much higher than the transverse direction.…”
Section: Materials and Scratching Methodsmentioning
confidence: 99%
“…The main function of the pyrolytic carbon interface is to protect the carbon fiber from damage during chemical vapor deposition, explaining the removal mechanism of the C f /SiC composite in this experiment does not distinguish it from the SiC matrix. 39 The main mechanical properties 38,39,44 of C f /SiC composite and its main compositions at room temperature are shown in Table 1. It can be found that the axial mechanical strength is much higher than the transverse direction.…”
Section: Materials and Scratching Methodsmentioning
confidence: 99%
“…Achieving precise control over surface morphology and atomic-level surface roughness is crucial for determining the performance and reliability of these devices 6 12 However, the fabrication of SiC wafers presents challenges due to its inherent hardness and chemical stability. Conventional chemical mechanical polishing (CMP) techniques have been widely employed for achieving surface planarization and controlling atomic-level surface roughness 9 , 13 …”
Section: Introductionmentioning
confidence: 99%
“…Niu et al [15] proposed a method to process BK7 glass by a vitrified bondfixed abrasive tool formed by the combination of a precision diamond abrasive and a coarse diamond abrasive. Feng [16][17][18] proposed a Polyvinyl alcohol/phenolic resin (PVA/PF) composite sol-gel tool to process SiC wafers. The abrasive tool showed excellent processing stability during processing.…”
Section: Introductionmentioning
confidence: 99%